Combined Effects of Nitrogen Deposition and Climate on Root-to-Shoot Ratios and Root Morphology in Temperate Tree Regeneration - Viktoria Dietrich; Jörg Niederberger; Nico Espadilha Patriarca; Meike E. Becker; Stefan Müller; Hannah Lorösch; Sophie Boll; Naima Hoque; Helena Jüngling; Nico Beck; Adrian Dierks; Pauline Ebert; et al. (Ecosystems, 2025)
Nitrogen (N) availability is known to interact with the drought tolerance in plants, but its effects on the morphological acclimation of forest trees to low precipitation have rarely been investigated. Based on a Germany-wide field-study design covering different combinations of climatic conditions and atmospheric N deposition, we harvested young trees up to 70 cm in height of Fagus sylvatica , Quercus petraea , Pseudotsuga menziesii , and Abies alba . We tested the hypothesis that high N deposition decreases the root/shoot ratio, alters fine root morphology (for example, by reducing specific root length of absorptive roots) and reduces mycorrhizal colonization rate, which are factors that would reduce the capacity for water uptake under drought. European beech showed reduced root/shoot ratios at high N deposition and reduced specific root length and mycorrhizal colonization of absorptive roots at sites with both high N deposition and low precipitation. These observations were consistent with the optimal portioning theory, as less investment in belowground biomass was required to meet the N demand at high N deposition. Sessile oak showed no effect of N deposition or mean annual precipitation on the parameters studied, indicating that the gradients studied were not large enough to cause changes. Douglas-fir and silver fir expanded their root systems with increasing N deposition, with higher specific root length in Douglas-fir and a trend towards higher root tip abundance in silver fir. Thus, in contrast to European beech, we found no indication that the tree's ability to cope with drought was reduced by high N deposition in sessile oak, Douglas-fir, and silver fir. The combined negative effect of drought and high N deposition on the root system in European beech as Central Europe’s most dominant tree species in the natural vegetation emphasizes the need for curtailing N emissions, especially from agriculture.

Subsequent primary neoplasms after childhood cancer therapy – design and description of the German nested case–control study STATT-SCAR - Peter Scholz-Kreisel; Cornelia Becker; Melanie Kaiser; Seyed Hamidreza Mahmoudpour; Mathias Voigt; Meike Ressing; Maria Blettner; Gabriele Calaminus; Katja Baust; Cathy Scholtes; Martin Zimmermann; Sylke Ruth Zeissig; et al. (Cancer Causes & Control, 2024)
Background Subsequent primary neoplasms (SPN) are among the most severe late effects and the second most frequent cause of death in childhood cancer patients. In this paper we introduce method and properties of the STATT-SCAR study (Second Tumor After Tumor Therapy, Second Cancer After Radiotherapy), which is a joint nested matched case–control study to evaluate the impact of chemotherapy (STATT) as well as radiotherapy (SCAR) on the risk of developing a SPN. Methods Based on the cohort of the German childhood cancer registry (GCCR), we selected patients diagnosed with a first neoplasm before age 15 or younger between 1980 and 2014. We selected those with a SPN at least half a year after the first neoplasm, and matched up to four controls to each case. Therapy data were acquired from various sources, including clinical study centers and treating hospitals. To analyze the impact of radiotherapy, organ doses were estimated by using reconstructed treatment plans. The effect of chemotherapy was analyzed using substance groups summarized after isotoxic dose conversion. Results 1244 cases with a SPN were identified and matched with 4976 controls. Treatment data were acquired for 83% of all match groups (one case and at least one control). Based on preliminary analyses, 98% of all patients received chemotherapy and 54% of all patients were treated with radiotherapy. Conclusions Based on our data, detailed analyses of dose response relationships and treatment element combinations are possible, leading to a deeper insight into SPN risks after cancer treatments. Trial registration The study is registered at the German clinical trial register (DRKS) under number DRKS00017847 [45].

Rapid fCO2 rise in the northern Barents Sea and Nansen Basin - Ylva Ericson; Agneta Fransson; Melissa Chierici; Elizabeth M. Jones; Ingunn Skjelvan; Abdirahman Omar; Are Olsen; Meike Becker (Progress in Oceanography, 2023)

Constraining the Oceanic Uptake and Fluxes of Greenhouse Gases by Building an Ocean Network of Certified Stations: The Ocean Component of the Integrated Carbon Observation System, ICOS-Oceans - Tobias Steinhoff; Thanos Gkritzalis; Siv K. Lauvset; Steve Jones; Ute Schuster; Are Olsen; Meike Becker; Roberto Bozzano; Fabio Brunetti; Carolina Cantoni; Vanessa Cardin; Denis Diverrès; et al. (Frontiers in Marine Science, 2019)